Penerapan Media Digital Wordwall sebagai Sarana Pengenalan ICT pada Siswa SDN Polagan 2 Pamekasan - Nailatur Rahmah; Ulfatul Isnaini; Rangga Fatih Asrori; Wulandari Ramadhani (Journal of Research in Education & Technology, 2025)
The research in this paper aims to find out, describe and study the application of digital media Wordwall as a means of introducing ICT to elementary school students. The use of the research approach in this journal is a descriptive qualitative approach with the use of methods in the form of interviews and participatory observations conducted at SDN Polagan 2 Pamekasan as a place of research. Then the findings are adjusted to the Triangulation Method Technique. The results of data analysis are carried out by data reduction, data presentation and drawing conclusions. This study produces results that show that the application of digital media in the form of Wordwall can increase student involvement, interest in learning and make it easier to understand learning materials while introducing students to technology. The response to the use of this digital media is very positive from both teachers and students, although during the study several challenges were still found in its application. The findings in this study indicate that the use of digital media has great potential to shape students' digital literacy from an elementary age. Therefore, further support and encouragement are needed to further optimize the application of digital media in learning activities, especially at the elementary school level.